CHARACTERIZATION, BENEFICIATION, AND REES EXTRACTION OF COAL BOTTOM ASH - Siti Rochani; Isyatun Rodliyah (Indonesian Mining Journal, 2022)
Rare earth elements are strategic materials. The elements have critical roles in meeting the needs of raw material for producing the modern industrial products. Most of the REE minerals is available in the form of associated minerals. One of them is coal. In terms of obtaining an overview regarding the possibility of coal to be a source of REEs, a research was carried out by beneficiating the bottom ash of the coal using a shaking table and a magnetic separator, and was followed by extracting the REEs using the alkaline fusion and leaching them using the nitric acid. The results showed that the bottom ash of gasified coal from the Palimanan pilot plant contained cerium, lanthanum, samarium, neodymium, praseodymium, europium, gadolinium, dysprosium, and yttrium, with a total content of 77.85 ppm. Concentrating the REEs using the shaking table and the magnetic separator result in a recovery of 32.96% and 50.5%, respectively. Extracting the REEs by alkaline fusion using NaOH as flux was not promising  while leaching with nitric acid was able to extract the REEs with various percentage extraction values, and the highest extraction for Neodymium was 73.46% under conditions of 2M nitric acid leaching and heated at 80°C.